Impact of COVID-19 Attention on Pharmaceutical Stock Prices Based on Internet Search Data - Xia, Yuanting; Hu, Wenxiu (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
Based on Baidu Index, 223 pharmaceutical stocks selected from the CSI 300 index from November 1, 2019 to June 8, 2020 were selected as research samples. Fama-French three-factor model and panel regression analysis were adopted to study the impact of investors’ attention to COVID-19 on the pharmaceutical stock market. Based on the three-factor model, this study explained the impact of investors’ increasing concern about the epidemic on the medical stock market from three dependent variables of return rate, trading volume and amplitude. The results show that investors’ attention to COVID-19 has a significant positive impact on the return, volume and amplitude of the pharmaceutical stock market during the same period.